2020
DOI: 10.3389/fpsyg.2020.592377
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Correlational Cuing While Controlling for Most-Recent-Pairing Effects

Abstract: Irrelevant aspects of the environment or irrelevant attributes of task-relevant stimuli can have important and reliable effects on behavior. When the specific values of an irrelevant attribute are correlated with different responses, a correlational-cuing effect is observed: faster and more accurate responses when the correlation is positive. Previous work has shown that this effect is not due to simple differences in how often the specific stimuli or attributes are being presented, and most explanations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 37 publications
(76 reference statements)
0
12
1
Order By: Relevance
“…On the one hand, this insight is consistent with the claim that Pavlovian conditioning effects in humans require explicit awareness of pairings (e.g., De Houwer, 2009 ; Lovibond & Shanks, 2002 ; Mitchell et al, 2009 ). On the other hand, this finding contrasts with previous explanations of contingency learning as being automatic, reflecting retrieval of incidental and transient stimulus–response bindings that do not require awareness ( C. G. Giesen et al, 2020 ; Schmidt et al, 2020 ; see also Jiménez et al, 2022 ; Rothermund et al, 2022 ; Xu & Mordkoff, 2020 ). Dissociating the roles of awareness-mediated learning and learning that is due to (direct or indirect) stimulus-based retrieval processes may therefore be a promising avenue for future research.…”
Section: Discussioncontrasting
confidence: 99%
“…On the one hand, this insight is consistent with the claim that Pavlovian conditioning effects in humans require explicit awareness of pairings (e.g., De Houwer, 2009 ; Lovibond & Shanks, 2002 ; Mitchell et al, 2009 ). On the other hand, this finding contrasts with previous explanations of contingency learning as being automatic, reflecting retrieval of incidental and transient stimulus–response bindings that do not require awareness ( C. G. Giesen et al, 2020 ; Schmidt et al, 2020 ; see also Jiménez et al, 2022 ; Rothermund et al, 2022 ; Xu & Mordkoff, 2020 ). Dissociating the roles of awareness-mediated learning and learning that is due to (direct or indirect) stimulus-based retrieval processes may therefore be a promising avenue for future research.…”
Section: Discussioncontrasting
confidence: 99%
“…That is, episodic response retrieval predicts facilitation (interference) if the retrieved response matches (conflicts with) the response that is required on the current trial (see Figure 1C ) – even if the retrieved response is infrequent in the current context – whereas the contingency learning account would predict facilitation or interference solely based on what is the more frequent response in the current context. Recent studies revealed that episodic retrieval is a better predictor of performance than contingency learning, and explains most if not all of the contingency learning effect ( Giesen et al, 2020 ; Schmidt et al, 2020 ; but see Xu & Mordkoff, 2020 ).…”
mentioning
confidence: 99%
“…In a study by Xu and Mordkoff (2020), however, a significant CL effect was found even after controlling for episodic retrieval. This result seems to indicate that episodic retrieval alone is not sufficient to explain the overall CL effect.…”
mentioning
confidence: 77%
“…In our study, we adopted some of the design features of Xu and Mordkoff (2020): First, we used a many-to-one mapping, assigning two colors to each response key, which allows us to separately control for the effects of both, episodic S-S and S-R retrieval. Second, we induced a contingency of medium strength between the irrelevant attribute and the correct color (5:1:1:1), which should produce some variance regarding the awareness of these contingencies while at the same time providing a sufficiently strong contingency effect.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation